Dinamika Epidemiologi Multidrug Resistensi (Ampicilin, Streptomycin and Tetracycline) pada Kucing Domestik di Wilayah Kota Surabaya Timur - Wibisono, Freshinta Jellia; Qurratu’ain, Seryna Hasna; Jalal, Ismul; Fardiansyah, Al; Isnaeni, Mutia; Mentari, Andi Oktaviana; Islam, Afif Fajrul; Wibisono, Freshindy Marissa; Widiasih, Dyah Ayu; Freshinta Jellia Wibisono (Acta VETERINARIA Indonesiana, 2025)
Antibiotic resistance in pets, especially cats, has become a serious global health challenge. The irrational use of antibiotics, whether excessive or inappropriate, accelerates the emergence of resistant bacteria that can potentially spread to humans and the environment. This study aims to identify the presence of antibiotic-resistant Escherichia coli and analyze its resistance patterns in domestic cats in East Surabaya. A total of 35 rectal swab samples were collected from pet cats and tested at the Veterinary Public Health Laboratory, Faculty of Veterinary Medicine, Wijaya Kusuma University, Surabaya. The samples were isolated using the selective MacConkey Agar medium and confirmed as Escherichia coli through Gram staining, biochemical tests, and antibiotic susceptibility testing. The results showed that 94.3% (33/35) of the samples contained Escherichia coli. Antibiotic susceptibility testing revealed resistance rates of 27% (9/33) to ampicillin, 24% (8/33) to streptomycin, and 12% (4/33) to tetracycline. Additionally, 9.1% (3/33) of the isolates were classified as multidrug resistance, showing resistance to all three antibiotics (AMP-TE-S). Other resistance patterns included AMP-S (6.1%) and TE-S (3.1%). The high resistance rate of Escherichia coli in domestic cats highlights the critical role of pets as potential reservoirs of resistant bacteria, which may impact human health through direct contact or environmental transmission. Therefore, raising awareness and educating pet owners and veterinary professionals on the prudent and responsible use of antibiotics is essential. The One Health approach, integrating human, animal, and environmental health, is a strategic measure to prevent the future spread of antimicrobial resistance.